2019
DOI: 10.1101/724062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine-scale seascape genomics of an exploited marine species, the common cockle Cerastoderma edule, using a multi-modelling approach

Abstract: 5 6 Running title: Seascape genomics of the common cockle 7 8ABSTRACT 26 Population dynamics of marine species that are sessile as adults are driven by oceanographic 27 dispersal of larvae from spawning to nursery grounds. This is mediated by life-history traits 28 such as the timing and frequency of spawning, larval behaviour and duration, and settlement 29 success. Here, we use 1725 single nucleotide polymorphisms (SNPs) to study the fine scale 30 spatial genetic structure in the commercially important co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…As well as being impractical to simulate 3D ocean circulation over decadal scales with a spatially high‐resolution (0.87–1.38 km) model, extreme cold and warm years are expected to represent a maximal range of residual flows and hence dispersal. This was confirmed by Coscia et al (2020), who conducted similar particle tracking simulations over several years (practical in this case since the domain was smaller—Irish Sea only), showing variability in dispersal between years that was similar to that simulated in this study. During the simulated cold year (1986), stratification caused by solar heating during the summer was relatively weak, hence, the associated density‐driven currents that are key to larval transport were also weak.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…As well as being impractical to simulate 3D ocean circulation over decadal scales with a spatially high‐resolution (0.87–1.38 km) model, extreme cold and warm years are expected to represent a maximal range of residual flows and hence dispersal. This was confirmed by Coscia et al (2020), who conducted similar particle tracking simulations over several years (practical in this case since the domain was smaller—Irish Sea only), showing variability in dispersal between years that was similar to that simulated in this study. During the simulated cold year (1986), stratification caused by solar heating during the summer was relatively weak, hence, the associated density‐driven currents that are key to larval transport were also weak.…”
Section: Methodssupporting
confidence: 90%
“…Such biophysical models have been used in conjunction with genetic studies of meta‐populations (e.g. Coscia et al, 2012, 2020; Gormley et al, 2015). Biophysical models will predict a range of plausible connectivities, for a specific period and given sufficient information on larval behaviour; although validation is challenging since larvae are too small to track.…”
Section: Introductionmentioning
confidence: 99%
“…3). Previous seascape genomic studies in temperate regions have frequently identified some measure of SST as the best predictor of genomic variation of marine invertebrates [9,11,12,25,28,67], which is most likely due to SST affecting both cellular processes, and life-history events such as spawning and larval development [63]. However, for P. angulosus, Trange and SSTmean best explained genomic variation, whereas SSSmean best explained the structure of C. punctatus.…”
Section: Different Environmental Drivers Of Selection Across Speciesmentioning
confidence: 99%
“…3). Previous seascape genomic studies in temperate regions have frequently identified some measure of SST as the best predictor of genomic variation of marine invertebrates [9,11,12,25,28,51], which is most likely due to SST affecting both cellular processes, and life-history events such as spawning and larval development [52]. However, for P. angulosus, Trange and SSTmean best explained genomic variation, whereas SSSmean best explained the structure of C. punctatus.…”
Section: Different Environmental Drivers Of Selection Across Speciesmentioning
confidence: 99%